2022
DOI: 10.1002/oby.23374
|View full text |Cite
|
Sign up to set email alerts
|

Beyond appetite regulation: Targeting energy expenditure, fat oxidation, and lean mass preservation for sustainable weight loss

Abstract: Lifestyle interventions can reliably produce and sustain only modest (~5%-10%) weight loss (1), necessitating other types of antiobesity interventions, such as pharmacotherapy, to address obesity management. Antiobesity medication development initially relied on observations of weight loss in agents approved for other indications, which resulted in troubled first-generation medications being used for weight management. However, new pharmacological treatments have been emerging based on an understanding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 161 publications
(246 reference statements)
1
35
0
Order By: Relevance
“…Despite the limited impact of SAR425899 on EE, the blunted metabolic adaptation observed in the SAR425899 group may be important for weight-loss maintenance [12]. Our findings are supported by our recent study in which we observed reduced metabolic adaptation to be a distinguishing phenotype in people who meet their predicted weight-loss targets versus those who do not [40].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Despite the limited impact of SAR425899 on EE, the blunted metabolic adaptation observed in the SAR425899 group may be important for weight-loss maintenance [12]. Our findings are supported by our recent study in which we observed reduced metabolic adaptation to be a distinguishing phenotype in people who meet their predicted weight-loss targets versus those who do not [40].…”
Section: Discussionsupporting
confidence: 87%
“…We also found greater FatOx and ketogenesis that were not due to the greater changes in weight and body composition. These metabolic effects of SAR425899 are important concepts for the further development of weight‐loss therapies because both low EE and low FatOx are risk factors for weight gain that impair loss of FM [12, 37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations